MODEL PENGELOLAAN SUMBER DAYA ALAM UNTUK SEBESARBESARNYA KEMAKMURAN RAKYAT - Kuswandi Kuswandi (Jurnal Hukum Mimbar Justitia, 2015)
Legal political management of Indonesia's natural resources is "the attitude and/or the attention of government/state of the management of natural resources in the form of policies as outlined in the Act and Regulation, where the rights of control by the state over natural resources as the primary basis and most fundamentally,its implementation by the state for the maximum kamakmuran people.Keywords: Economic Liberalization, Right to Control by the State, PublicWelfare.